Gagasan Pengembangan Augmented Reality pada Buku Bacaan sebagai Upaya Meningkatkan Minat Baca Siswa (Adaptasi Percepatan Literasi dari Korea Selatan) - Arifah Suryaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
Many learning media models of Augmented Reality were developed in South Korea. Because such learning media are able to support students' understanding more than just reading texts. In conditions of low literacy levels in Indonesia while the trend of technological and information advancements in Indonesia is so rapid, especially those that lead to the industrial revolution 4.0, it is necessary to propose the application of Augmented Reality to reading books with the aim of becoming an effort to increase students' reading interest in Indonesia and especially in the school where the author teaches. The stages in the development of this AR-based book use the Multimedia Development Methodology sourced from Luther, with six stages namely: Concept (concept), Design (design), Collecting material (material collecting), Making (assembly), Testing (testing), and Distribution (distribution). To create developments in the world of education and increase the attractiveness and effectiveness of learning, Augmented Reality technology can be utilized in the learning process both inside and outside of school. In order to achieve this, collaboration between digital creative actors or the IT profession and collaborators or teachers in creating AR media is needed in order to match the material and information to be conveyed.